An Electronic Alert for HIV Screening in the Emergency Department Increases Screening but not the Diagnosis of HIV - Schnall, R.; Liu, N.; Sperling, J.; Green, R.; Clark, S.; Vawdrey, D. (Applied Clinical Informatics, 2014)
Objective: Based on US. Centers for Disease Control and Prevention recommendations, New York State enacted legislation in 2010 requiring healthcare providers to offer non-targeted human immunodeficiency virus (HIV) testing to all patients aged 13–64. Three New York City adult emergency departments implemented an electronic alert that required clinicians to document whether an HIV test was offered before discharging a patient. The purpose of this study was to assess the impact of the electronic alert on HIV testing rates and diagnosis of HIV positive individuals.Methods: During the pre-intervention period (2.5–4 months), an electronic “HIV Testing” order set was available for clinicians to order a test or document a reason for not offering the test (e.g., patient is not conscious). An electronic alert was then added to enforce completion of the order set, effectively preventing ED discharge until an HIV test was offered to the patient. We analyzed data from 79,786 visits, measuring HIV testing and detection rates during the pre-intervention period and during the six months following the implementation of the alert.Results: The percentage of visits where an HIV test was performed increased from 5.4% in the pre-intervention period to 8.7% (p<0.001) after the electronic alert. After the implementation of the electronic alert, there was a 61% increase in HIV tests performed per visit. However, the percentage of patients testing positive per total patients-tested was slightly lower in the post-intervention group than the pre-intervention group (0.48% vs. 0.55%), but this was not significant. The number of patients-testing positive per total-patient visit was higher in the post-intervention group (0.04% vs. 0.03%).Conclusions: An electronic alert which enforced non-targeted screening was effective at increasing HIV testing rates but did not significantly increase the detection of persons living with HIV. The impact of this electronic alert on healthcare costs and quality of care merits further examination.Citation: Schnall R, Liu N, Sperling J, Green R, Clark S, Vawdrey D. An electronic alert for HIV screening in the emergency department increases screening but not the diagnosis of HIV. Appl Clin Inf 2014; 5: 299–312 http://dx.doi.org/10.4338/ACI-2013-09-RA-0075
Keywords: HIV testing; electronic alert; electronic order set; screening test